1998
DOI: 10.1016/s0889-8553(05)70008-x
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Nutrition

Abstract: This article briefly reviews the literature supporting the use of enteral nutrition, which appears to be the preferred method of nutritional support in critically ill patients. Patients who benefit the most from this type of support, as well as the administration and route preferences in enteral nutrition, are discussed. In addition, the different types of enteral formulas and the more frequently associated complications that occur with tube feedings are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Clinical practice favors early administration of enteral nutrition (EN) to critically ill patients. [1][2][3][4][5][6][7][8][9] Nasogastric and orogastric feeding tubes are frequently the routes for intragastric EN. Tolerance to intragastric EN is monitored by serially measuring the volume of aspirated gastric residual (elevated volumes represent intolerance) and assessing the patient's abdomen for tenderness and presence of bowel sounds.…”
mentioning
confidence: 99%
“…Clinical practice favors early administration of enteral nutrition (EN) to critically ill patients. [1][2][3][4][5][6][7][8][9] Nasogastric and orogastric feeding tubes are frequently the routes for intragastric EN. Tolerance to intragastric EN is monitored by serially measuring the volume of aspirated gastric residual (elevated volumes represent intolerance) and assessing the patient's abdomen for tenderness and presence of bowel sounds.…”
mentioning
confidence: 99%
“…2,10,11,24,26 Recent studies on immunoprotective enteral diets have shown that they provide both metabolic and immunological support for such patients. [9][10][11]27 Choudhry et al suggested that a diet enriched with immunocompounds, such as arginine, fish oil, nucleotides, and glutamine can prevent T-cell dysfunction after thermal injury. 28 Gottschlich et al also demonstrated that a diet enriched with immunomodulatory components, such as arginine and omega-3 fatty acids, reduces wound infection rates and hospitalization in patients with thermal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Giving patients an enteral diet enriched with immunomodulatory components such as arginine, glutamine, and omega-3 fatty acids has been shown to reduce the incidence of septic complications and the hospital stay in critically ill patients. [9][10][11][12] One such treatment involves probiotics, which are defined as food or drugs containing live microbes that have a beneficial physiological effect on the host. Previous studies suggest that lactic acid bacteria stimulate the immune Abstract Purpose.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In most cases, enteral formulas containing standard protein sources are sufficient to maintain nitrogen balance and avoid hepatic encephalopathy. 13 However, in patients with protein intolerance demonstrated by severe encephalopathy, a BCAA-enriched enteral formula may be better tolerated and allow achievement or near-achievement of nitrogen balance without exacerbating encephalopathy. Use of this type of formula should be limited to patients with severe encephalopathy who have not responded to aggressive therapy with lactulose and neomycin.…”
Section: Liver Diseasementioning
confidence: 99%